Soybean seed oil: Nutritional composition, healthy benefits and commercial applications - de Almeida Chuffa, Luiz Gustavo [UNESP]; Vieira, Fabrício Rocha [UNESP]; da Silva, Daniela Alessandra Fossato [UNESP]; Franco, Danilo Miralha [UNESP] (My University, 2014)
The vegetable oils are dietary sources of sterols, vitamin E, and unsaturated fatty acids. The fatty acid composition and the content of an unsaponifiable substance in oilseeds depend on the variety of plant, degree of ripening seeds and the climatic conditions. Vegetable soybean (Glycine max (L.) Merr.) is an annual dicotyledonous plant belonging to the family of Fabaceae (Leguminosae) in the genus; their genotypes are divided into two categories: large-seeded and small-seeded. The largeseeded types are used for the fresh market in urban areas, whereas smallseeded types are used to make soybean sprouts. There are several groups of nutrients in soybean that are currently under investigation for healthy benefits, such as flavonoids and isoflavonoids, phenolic acids, phytoalexins, phytosterols, proteins and peptides, and saponins. In addition, soybeans are also an important source of minerals copper, manganese, molybdenum, phosphorus, potassium, B vitamin, and omega- 3 fatty acids (alpha-linolenic acid). Replacing meat and dairy with soy may decrease total cholesterol intake by about 123 mg/day and saturated fat by about 2.4 g/day. These changes would reduce the risk of developing cardiovascular diseases, and even the cancer. Soybean oil is the edible oil extracted from soybean seeds, largely used as cooking oil in the world according to the US agricultural services. Dry soybean seeds compose 18-20% of extractable oil by weight. The seeds are then subject to pressing to obtain oil and the residue is used as animal feed. The crude soybean oil is yellow in color and contains moisture, lecithin, free-fatty acids, and some volatile compounds. These impurities have to be removed to obtain acceptable standard oil. Soybean oil has a good lipid profile with saturated, monounsaturated and polyunsaturated fats in healthy proportions (SFA:MUFA:PUFA=16:24:58). Linoleic acid (omega-6) is the major polyunsaturated fatty acid found in oil; phytosterols, especially B-sitosterol, inhibit cholesterol absorption and reduce blood LDL-cholesterol levels by 10% to 15%; anti-oxidant vitamin E, a powerful lipid soluble vitamin, is important to maintain the integrity of cell membranes and protect them from harmful reactive oxygen-free radicals; vitamin K, an essential element in promoting bone formation and strengthening, and neuronal protection in the brain. More recently, genetic engineering is becoming an important tool to produce different and exotic oils derived from a diversity of plants in domesticated and commercial seeds-like soybean, by using genetic transformation. This technique has attracted commercial interest and can be employed to produce seeds with the chemical composition of the oil, enriched with specific substances that can be used as an alternative therapy in the treatment of various diseases. This chapter will present the nutritional composition and healthy benefits of soybean oil and some potential commercial implications.